Clinical researchPica: a frequent symptom in iron deficiency anemia - Beyan, Cengiz; Kaptan, Kürşat; Ifran, Ahmet; Beyan, Esin (Archives of Medical Science, 2009)
Introduction: Pica is the habitual ingestion of non-nutritive substances. The aim of the study is to investigate the frequency and types of pica and the relationship of pica with patient characteristics. Material and methods: This descriptive prospective study was conducted between October 2005-December 2006. 119 patients with iron deficiency anemia (IDA) were included. The data were collected by using a standard questionnaire form. Results: In this study, a total of 119 IDA patients whose mean age was 37.0 ±11.5 (mean ± SD) (range 15-72 years) were investigated. Ninety-four of the cases had pure IDA, 19 additional vitamin B12 deficiency and six pregnancy. The frequency of pica was 34.4% in the study group, 38.3% in pure IDA patients, 15.8% in iron and vitamin B12 deficiency patients and 33.3% in pregnants. Pica was more prevalent in pure IDA patients than those with additional vitamin B12 deficiency (p = 0.048). Age was not a significant factor in pica frequency. There was no relationship between the severity of anemia and the frequency of pica. No difference has been observed between complete blood count parameters of IDA patients with and without pica, apart from a borderline difference in mean platelet volume (p = 0.057). Conclusions: As a result, pica is a frequent finding in IDA, and patients with and without pica have similar characteristics.